First record of the interaction between the arthropod-pathogenic fungus Gibellula and a new species of harvestman Auranus (Stygnidae) narrowly endemic to the Brazilian rain forest - Villanueva-Bonilla, German Antonio; Araújo-Da-Silva, Luiz Paulo; Vasconcellos-Neto, João; Moura Sobczak, Jullyana Cristina Magalhães Silva; Fonseca, Emily Oliveira; de Sousa Nóbrega, Francisco Ageu; Pires, Joedson Castro; Arruda, Italo Diego Paiva; Dasilva, Marcio Bernardino; Sobczak, Jober Fernando (Zootaxa, 2021)
Harvestmen are one of the largest groups of arachnids with more than 6,500 species distributed in 1,500 genera and 50 families. However, the interactions between harvestmen and arthropod-pathogenic fungi have rarely been studied. Certain previous studies report that fungal attack represents one of the most important factors for the mortality of harvestmen, but the fungus has rarely been identified, and most of the important information about the fungus-host interactions remains unrecorded. In the present study, we have described the new species Auranus quilombola sp. nov. and reported its interactions with the arthropod-pathogenic fungus Gibellula sp. Auranus quilombola sp. nov. belongs to the family Stygnidae, and it is endemic to the humid mountain forests of Ceará state, Brazil in an area of endemism known as Brejos Cearenses. The species is related to five other species of Auranus, all of which have been recorded from the Amazon rainforest. A taxonomic description of this new species and its biogeographic implications have also been discussed in this paper.